The applications of aerial photography, photogrammetry and photo-interpretation in the planning process - Meadows, P L (School of Architecture, Planning and Geomatics, 2021)
To date aerial photography and associated photogrammetric and photo-interpretation techniques have played but a limited role in the planning process. In this study their dual role (i) as a base medium and (ii) as a source of data is investigated bearing in mind the requirements of planning data and certain inherent defects of conventional maps in the planning process. Having considered certain pertinent technical aspects of aerial photography and associated techniques, especially modern developments such as orthophotos, use of multi-emulsion photography, automated data extraction and automated data processing techniques, the application of these techniques is discussed in greater detail in respect of the dual role mentioned earlier. Aerial photographs are shown to be of considerable value to the planner as an analytic tool and a powerful source of data when dealing with such topics as feasibility studies, land use, resource surveys, urban and regional research and analysis, urban history, urban and rural administration, site evaluation, transportation and other. branches of engineering, urban sociology and economics, as well as urban aesthetics. Aerial photographic data adequately meets the data requirements of the planning process and furthermore lends itself to modern automatic data processing methods. The modern improved forms of photography, i.e. photomaps, orthophotos, etc. have definite advantages over conventional maps insofar as a base medium in planning is concerned, and the wider use of aerial photographs and products is anticipated when planners become more aware of their universal application and versatility.